Offshore financial centres in the Caribbean (UN. ECLAC/CDCC Port of SpainTT, 1995)
Describes the basic services provided by offshore financial centres. Provides an outline of the perceived benefits and costs to the host countries and the offshore companies. Supplies national data relating to the number of registered companies, government revenue and employment in the main Caribbean offshore centres. Presents case studies on Barbados and the Netherlands Antilles which elaborate the developments in these jurisdictions. Looks at possible future contributions of the offshore financial centre to national development.
DC